Analysis of the rebound effect and interactive between fiscal and monetary policy on the General economic equilibrium (IS-LM) - كاظم فريد جواد; عبيد باسم خميس (Journal of Economics and Administrative Sciences, 2018)
Will address this research interaction and coordination between fiscal and monetary policies and the impact of this interaction and coordination on economic stability and growth، and how the financial implications of monetary policy may stimulate action monetary policy and treatment side effects and the nature of responsiveness and bounce between procedures both two policies and their impact on the balance of overall economic and explained in the folds of searchjustifications coordination and the extent necessary in order to address the imbalances in economic activity through twinning actions of monetary and fiscal، has embodied this coordination and interaction between policies and their impact mutual consistent and inconsistent when studying balance general economic and pillars of balance in the money market and the balance in the market commodity (Is-Lm) .The balance monetary and commodity introductions essential to balance the general economic with origin and dimension Keynesian who put its basic idea balance economists Hekes and Hansen in their analysis of the balance of Keynesian Economics (income model simplex) and then was developed model to model (Is-Lm) thanks to their contributions theory and summarized tie between aggregate demand cash and aggregate supply commodity which plays monetary policy role "influential" and sensitive "in aggregate demand cash (monetary value of goods and services) also affect fiscal policy effectively in the overall width of the commodity (content Commodity money) and both two policies by its tools and policies different leaves effects mutually responsive about the purpose or mutual feedback effects on the target ... that stable economic balance is a viable case to restore balance in the event that this balance to the imbalance by self-forces and the unstable economic balance is non-viable state to restore balance، but remain in the folds oscillate between imbalance and stabilize the rates of certain economic use and output and prices .